Detection of antibodies against Toxoplasma gondii in a domestic ferret (Mustela putorius furo) in Lima, Peru - Lescano G., Jesús (2017)
It is known that domestic ferrets (Mustela putorios furo) are susceptible to toxoplasmosis; however, information is scarce. This report describes the case of a 6.5 years old female ferret received at the Wild and Exotic Animals Clinic of the Universidad Nacional Mayor de San Marcos (Lima, Peru), which presented recent anorexia and diarrhoea. Physical examination revealed dehydration, bradycardia, hypothermia, and lethargy. Haematology revealed leucocytosis, neutrophilia, and thrombocytopenia. Serum biochemistry revealed hypoglycaemia and increased creatine kinase. Anti-Toxoplasma IgM and IgG were found by Indirect Hemagglutination assay. The ferret died two days after therapy was established and post mortem examination was not allowed.